Genotyping and molecular characteristics of multidrug-resistant Mycobacterium tuberculosis isolates from China. Issue 4 (April 2015) - Zhang, Zhijian; Lu, Jie; Liu, Min; Wang, Yufeng; Qu, Geping; Li, Hongxia; Wang, Jichun; Pang, Yu; Liu, Changting; Zhao, Yanlin
Summary Objectives The aim of this study was to explore the population structure of multidrug-resistant (MDR) tuberculosis strains and distribution of resistance-associated nucleotide alteration among the different genotype MDR strains in China. Methods The genotypes of 376 MDR strain were analyzed by 15-loci MIRU-VNTR and RD105 deletion-targeted multiplex PCR (DTM-PCR) method. In addition, all the MDR isolates were sequenced for genetic mutations conferring rifampicin (rpoB) and isonizid resistance (katG, inhA and oxyR-ahpC). Results Among the 376 MDR isolates, 261 (69.4%) belonged to Beijing genotype, including 177 modern Beijing strains (67.8%) and 84 ancient Beijing (32.2%) strains. The percentages of streptomycin-resistant, kanamycin-resistant, pre-XDR and XDR TB in modern Beijing genotype were significantly lower than ancient genotype (P < 0.05). The Beijing MDR strains had significantly higher proportions of ofloxacin-resistant and pre-XDR isolates than non-Beijing strains (P < 0.01). In addition, the clustering rate of modern Beijing strains was significantly higher than that of ancient Beijing strains (46.3% vs. 11.9%, P < 0.01). 94.7% and 79.3% of MDR isolates harbored genetic mutations conferring rifampicin and isonizid resistance, respectively, and the most prevalent mutation was located in codon rpoB531 and katG315. In addition, the rpoB531 and katG mutation were more frequently observed among Beijing genotype strains than non-Beijing strains, while non-Beijing genotype showed stronger association with isolates lacking mutation in rifampicin resistance determination region (P < 0.05). Conclusions Our findings demonstrated that ancient Beijing MDR strains were associated with drug resistance, while modern Beijing MDR strains were more likely to be clustered.